Alterations in vaginal microbiota among pregnant women with COVID‐19. Issue 1 (16th September 2022) - Celik, Ebru; Ozcan, Gulin; Vatansever, Cansel; Paerhati, Erxiati; Kuşkucu, Mert A.; Dogan, Ozlem; Cekic, Sebile Guler; Ergonul, Onder; Gürsoy, Attila; Keskin, Özlem; Can, Fusun
Abstract: The maintenance of vaginal microbiota is an important factor to achieve optimum pregnancy outcomes. The study aims to describe the alterations in the composition of vaginal microbiota in pregnant women with coronavirus disease 2019 (COVID‐19). This was a prospective case‐control study. Vaginal swabs were collected from uninfected pregnant women ( n  = 28) and pregnant women with COVID‐19 ( n  = 19) during the active phase of infection and within a month after recovering from infection. The vaginal microbiota on the swabs was examined by 16S rRNA gene sequencing. Shannon index indicates that alpha diversity is significantly higher in women with COVID‐19 ( p  = 0.012). There was a significant decrease in Firmicutes ( p  = 0.014) with an increase in Bacteroidota ( p  = 0.018) phyla and a decrease in Lactobacillus ( p  = 0.007) genus in women with COVID‐19 than those of uninfected pregnant women. The relative abundance of L. crispatus, L. iners, L. gasseri, and L. jensenii were lower in the COVID‐19 group than in uninfected pregnant women. In subgroup analysis, the amount of Ureaplasma spp. was higher in women with moderate/severe than those of asymptomatic/mild disease ( p  = 0.036). The study revealed that vaginal dysbiosis with low abundance of Lactobacillus species occurred in pregnant women infected with severe acute respiratory syndrome coronavirus‐2. These findings may lead to new studies to elucidate the risk of pregnancy adverse outcomes related to COVID‐19.